Spatially distinct binding of Cdc42 to PAK1 and N-WASP in breast carcinoma cells. - Parsons, M; Monypenny, J; Ameer-Beg, S; Millard, T; Machesky, L; Peter, M; Keppler, MD; Schiavo, G; Watson, R; Chernoff, J; Zicha, D; Vojnovic, B; et al. (2005)
While a significant amount is known about the biochemical signaling pathways of the Rho family GTPase Cdc42, a better understanding of how these signaling networks are coordinated in cells is required. In particular, the predominant subcellular sites where GTP-bound Cdc42 binds to its effectors, such as p21-activated kinase 1 (PAK1) and N-WASP, a homolog of the Wiskott-Aldritch syndrome protein, are still undetermined. Recent fluorescence resonance energy transfer (FRET) imaging experiments using activity biosensors show inconsistencies between the site of local activity of PAK1 or N-WASP and the formation of specific membrane protrusion structures in the cell periphery. The data presented here demonstrate the localization of interactions by using multiphoton time-domain fluorescence lifetime imaging microscopy (FLIM). Our data here establish that activated Cdc42 interacts with PAK1 in a nucleotide-dependent manner in the cell periphery, leading to Thr-423 phosphorylation of PAK1, particularly along the lengths of cell protrusion structures. In contrast, the majority of GFP-N-WASP undergoing FRET with Cy3-Cdc42 is localized within a transferrin receptor- and Rab11-positive endosomal compartment in breast carcinoma cells. These data reveal for the first time distinct spatial association patterns between Cdc42 and its key effector proteins controlling cytoskeletal remodeling.